PLACENTAL THICKNESS AS PREDICTOR OF FETAL WEIGHT IN SECOND AND THIRD TRIMESTER IN SINGLETON PREGNANCIES - Vaish, Paarth; kharka, Latha V; Pal, Srabanti (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to find out correlation between placental thickness and fetal weight in singleton pregnancies. Methods: One hundred and twenty patients with singleton pregnancies between 14 and 42weeks of gestation were included in this study on the basis of a predefined inclusion and exclusion criteria. Gestational age and fetal weight were determined by biometry. Placental thickness was measured at the level of cord insertion. Correlation between placental thickness and fetal weight was assessed using Pearsons coefficient. p<0.05 was taken as statistically significant. Results: The mean age of the studied cases was found to be 26.12±6.38 years. The mean gestational age of studied cases was found to be 28.62±9.12 years. In majority of the cases (46.67%), placenta was anterior in location followed by posterior (31.67%). In 14 (11.67%) cases, placenta was found to be fundal. In 3 cases (2.50%), placenta was found to be covering internal Os (Placenta Previa). The mean placental thickness varied from 13.32 mm (at 12 weeks) to 36.34 mm (42 weeks). The thickness gradually increased from 13.32 mm to reach a nadir of 37.22 at 38 weeks after which there was slight decline in placental thickness. The analysis of correlation between placental thickness and fetal weight showed that there was a strong correlation between mean placental thickness and fetal weight from 14 weeks till 37 weeks of gestation. Conclusion: There is a positive correlation between placental thickness and fetal weight in second and third trimester of singleton pregnancies.